2023
DOI: 10.1002/smll.202306191
|View full text |Cite
|
Sign up to set email alerts
|

Chemotactic Micro/Nanomotors for Biomedical Applications

Xue Xia,
Yue Li,
Xiangyu Xiao
et al.

Abstract: In nature, many organisms respond chemotactically to external chemical stimuli in order to extract nutrients or avoid danger. Inspired by this natural chemotaxis, micro/nanomotors with chemotactic properties have been developed and applied to study a variety of disease models. This chemotactic strategy has shown promising results and has attracted the attention of an increasing number of researchers. This paper mainly reviews the construction methods of different types of chemotactic micro/nanomotors, the mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 145 publications
(329 reference statements)
0
2
0
Order By: Relevance
“…The evolution of MNMs has seen significant progress from fundamental locomotion at micro/nanoscale to their biomedical applications in in vivo biomedical contexts. 105 The emergence of MNM swarms has attracted increasing attention, leading to investigations into various modes of manipulation. 84,92,93 Some of these swarms have demonstrated practical applications in vivo and shown clear advantages over single MNMs.…”
Section: Discussionmentioning
confidence: 99%
“…The evolution of MNMs has seen significant progress from fundamental locomotion at micro/nanoscale to their biomedical applications in in vivo biomedical contexts. 105 The emergence of MNM swarms has attracted increasing attention, leading to investigations into various modes of manipulation. 84,92,93 Some of these swarms have demonstrated practical applications in vivo and shown clear advantages over single MNMs.…”
Section: Discussionmentioning
confidence: 99%
“…These nanoparticles can semiactively approach tumor sites, thereby facilitating the aggregation of nanomedicines at tumor sites. [144] In 2023, Dong et al [145] reported mPPy@COF-Por nanomotors that generate a localized 808 nm laser-excited photothermal effect and thermal gradient. A self-induced thermophoretic force actively drives the directional motion of the nanomotors, which is considered beneficial for tumor penetration.…”
Section: Targeted Delivery and Therapymentioning
confidence: 99%